Doped YVO₄ crystals: growing, properties and applications - Matrosov, V.N.; Matrosova, T.A.; Kupchenko, M.I.; Yalg, A.G.; Pestryakov, E.V.; Kisel, V.E.; Scherbitsky, V.G.; Kuleshov, N.V. (Functional Materials, 2005)
Results of growing YVO₄ crystals doped with Nd, Er, Yb, Сr are given. Problems of obtaining crystals of high optical quality are discussed. Spectral and generating characteristics of these crystals are discussed. Spectral data of Сr⁵⁺ in YVO₄ are given. They suggest to create active laser medium with passive Q-switching in single Nd³⁺, Сr⁵⁺:YVO₄ crystal.